ADAB BERBICARA DALAM AL-QUR'AN DAN IMPLEMENTASINYA DI SDIT AL BIRUNI MANDIRI JIPANG MAKASSAR - Rati Astuti; Muhammad Rusydi Khalid; Halimah Basri (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
This writing talks about implementation of spoken moral insight in Quran at one of private school in Makassar, called SDIT Al Biruni Mandiri Jipang Makassar. In view of this era the morals of children have declined that proven by too many incidents were not supposed to happen. That happened because teaching and practicing about morals began to diminish so the student treats his teacher as he treats his friend. Consequently, in view of Quran is guidance of the mankind which talks about all of life problems in this world and here after, So, the main standard to set the concept as a rule that should be adhered to. The author is collecting information by learning quran verse was using term